A tensão entre proximidade e distância no segundo momento do pensamento de Nietzsche - SILVA, André Diogo Santos da (Universidade Federal do Pará, 2018)
Reflections on proximity and distance occur mainly in the second moment of Nietzsche’s thinking (1876 to 1882), in so far as he developed, around 1879, the idea of “doctrine of the nearest things”, and, some years later, in 1882, the notion of “artistic distance”. However, in this period he also criticizes the idea of opposition, since this concept alludes to a metaphysical philosophy. Another concept found in Nietzschean philosophy that would also express a relation between antagonisms is the idea of tension, which reflects a greater dynamicity. Thus, the problem of the present research consists in the following question: could it be possible to characterize the relation between the concepts of proximity and distance, identified in works belonging to the second moment of Nietzsche’s writings, as a tension, and not only an opposition (in view of the philosopher’s criticism of this idea)? From this general problem, the following specific objectives were established: 1. To delimit the specificity of the tension, mainly from the comparison with the concepts of opposition and antagonism; 2. To characterize proximity through the idea of the “doctrine of nearest things” and other related ideas, especially in the two volumes of Human, all too human and in The Down; 3. Find traces of the concept of distance in the Nietzschean writings, highlighting The Gay Science, a work that contains reflections on “artistic distance”; 4. To justify a tension between the previous concepts, identifying texts where Nietzsche suggests this relation (and not an opposition) between proximity and distance. These four objectives were developed through a bibliographical and historical-philological methodology, focusing mainly on the analysis of Nietzsche’s writings at the second moment of his intellectual production. As one of the results of the present investigation, we highlight the one that points out that the tension between proximity and distance in Nietzsche is observed more intensely, first, in the scope of knowledge – in which the thinker needs, one moment, to approach the object, the next to distance himself from his passionate quest for knowledge – and then, in the sphere of friendship – which differs from a simple “love of neighbor”, for in a high friendship the individual is also capable of distancing himself from his friend.